Antimicrobial Susceptibilities of Yersinia enterocolitica Biotype 4, Serotype O:3 - Hammerberg, S. (1977)
Agar dilution antimicrobial susceptibility tests were carried out against recent clinical isolates of Yersinia enterocolitica biotype 4, serotype O:3. Aminoglycosides and co-trimoxazole were the most active drugs. All isolates were resistant to ampicillin, carbenicillin, cloxacillin, and erythromycin.